2019
DOI: 10.1038/s41398-019-0485-7
|View full text |Cite|
|
Sign up to set email alerts
|

Alzheimer’s disease polygenic risk score as a predictor of conversion from mild-cognitive impairment

Abstract: Mild-cognitive impairment (MCI) occurs in up to one-fifth of individuals over the age of 65, with approximately a third of MCI individuals converting to dementia in later life. There is a growing necessity for early identification for those at risk of dementia as pathological processes begin decades before onset of symptoms. A cohort of 122 individuals diagnosed with MCI and followed up for a 36-month period for conversion to late-onset Alzheimer’s disease (LOAD) were genotyped on the NeuroChip array along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 43 publications
2
83
0
1
Order By: Relevance
“…Annotation: ***p-value of association < 5 × 10 −6 ; **p-value of association < 5 × 10 −4 ; *p-value of association < 5 × 10 −2 . studies showed that PRS of AD not only associated with increased risk of AD, but also with neuropathological hallmarks of AD, lifetime risk and the age at onset in both APOE ε4 carriers and non-carriers 28,29,[51][52][53][54][55] . We now add that, using our unique cohort of cognitively healthy centenarians, the PRS for AD also associates with resilience against AD at extremely old ages.…”
Section: Discussionmentioning
confidence: 99%
“…Annotation: ***p-value of association < 5 × 10 −6 ; **p-value of association < 5 × 10 −4 ; *p-value of association < 5 × 10 −2 . studies showed that PRS of AD not only associated with increased risk of AD, but also with neuropathological hallmarks of AD, lifetime risk and the age at onset in both APOE ε4 carriers and non-carriers 28,29,[51][52][53][54][55] . We now add that, using our unique cohort of cognitively healthy centenarians, the PRS for AD also associates with resilience against AD at extremely old ages.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, we aim to explore other methods to generate polygenic models to predict Alzheimer's disease. Although it is known that age and gender are important predictors of AD (for example [19]), we are focused on predicting AD from GWAS data only to show a potential computational strategy. In this context, using GWAS only, we improved about 5% on AUC by using specific information from misclassified samples either in the train or test sets.…”
Section: Discussionmentioning
confidence: 99%
“…There are many approaches to generate multivariate predictive models from GWAS data [17]. The polygenic risk score (PRS) is the most popular approach and has been applied to AD several times [17][18][19][20][21][22]. PRS is a sum of univariate estimated coefficients; thus, it is easily interpreted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the PRS accounts for the small effects of a large number of SNPs which still contribute to disease risk, successfully capturing the polygenicity of a disease. PRS has been widely used for identifying and/or predicting an individual's disease risk ( Escott-Price et al, 2015a ; Escott-Price et al, 2015b ; Ibanez et al, 2017 ) and for studying genetic overlap between disorders traits ( Chaudhury et al, 2019 ; Creese et al, 2019 ; McLaughlin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%